Ella Platinum Beauty Clinic Marketing Strategy to Increase Customer Loyalty in Surakarta City - Wihastuti, Ameyla; Adiyani, Rini; Darmaningrum, Kurniawati (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study aims to analyze the marketing strategies implemented by Ella Platinum Beauty Clinic in increasing customer loyalty in Surakarta City Methodology: This research uses a Quantitative method with a questionnaire research instrument with the SPSS 25 application. This type of research is Descriptive research. This research uses a survey and using a technique Purposive Sampling. Main Findings: Analyzing the influence of service quality, product quality and facilities partially and simultaneously on customer loyalty at the Ella Platinum Beauty Clinic. Novelty/Originality of this study: The impotance of this research is not only in its contribution to the development of marketing science, but also in its practical value for Ella Platinum Beauty Clinic. By understanding the factors that influence customer loyalty, clinic management can formulate more effective strategies to increase customer loyalty. This can strengthen the position of Ella Platinum Beauty Clinic in the era of competitive market competition.